Coup d'état in Africa and stock market returns: the case of French companies - Boungou, W; Gupta, P; Wahyono, B (Elsevier, 2024)
This article studies the impact of recent coups d'état in French-speaking Africa on the stock market performance of French companies. Using stock prices of 197 French companies over the period September 2020 to September 2023, our results highlight a negative impact of coups d'état on the stock market performance of French companies. We also observe the heterogeneity of these companies' reactions depending on: (i) the country affected by the coup; (ii) the companies' sector of activity; (iii) coups d'état with reshuffle or change of political regime; (iv) pro- or anti-France post-coup actions. In so doing, this article provides the first evidence of the impact of recent coups in Africa outside the affected territories.